2021
DOI: 10.1007/s13753-021-00372-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Drivers for Mainstreaming Nature-Based Solutions for Flood Risks: The Case of South Korea

Abstract: Nature-based solutions (NBS) are seen as a promising adaptation measure that sustainably deals with diverse societal challenges, while simultaneously delivering multiple benefits. Nature-based solutions have been highlighted as a resilient and sustainable means of mitigating floods and other hazards globally. This study examined diverging conceptualizations of NBS, as well as the attitudinal (for example, emotions and beliefs) and contextual (for example, legal and political aspects) barriers and drivers of NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Lack of public awareness and knowledge discrepancy regarding naturebased health is also an important barrier. 38 IUCN's nature 2030 programme calls for equitable distribution of naturebased solutions for all. Notwithstanding these barriers, it remains an evidence-based fact that nature has been playing a harmonious role in the world of health, creating a connection between individual and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of public awareness and knowledge discrepancy regarding naturebased health is also an important barrier. 38 IUCN's nature 2030 programme calls for equitable distribution of naturebased solutions for all. Notwithstanding these barriers, it remains an evidence-based fact that nature has been playing a harmonious role in the world of health, creating a connection between individual and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is particularly likely if coalition-building efforts with sceptics focus on adopting their solutions without addressing their underlying fears and concerns. Such an approach may lead to an increase in hybrid solutions that combine green and grey measures, potentially opening the door for accusations of NBS as a green-washing vehicle (Anderson et al, 2022;Han and Kuhlicke, 2021).…”
Section: Synthesismentioning
confidence: 99%
“…Other studies have shown that policymakers as well as practitioners also tend to underestimate the efficacy of NBS. For example, policymakers and practitioners have more reliance on technical measures than nature‐based solutions compared to the people in academia from their interviews (Han & Kuhlicke, 2021; Wolf et al., 2021). In cases where flood risks were considered to be high or where a locality has experienced severe flooding in the past, technical measures were preferred by the policymakers (Brillinger, Dehnhardt, Schwarze, & Albert, 2020).…”
Section: Introductionmentioning
confidence: 99%